As Web esquetes do porta dos fundos e a atenção do espectador: análise de elementos de linguagem audiovisual - SOZIGAM, Priscila (2017)
This research aims to understand which audiovisual language elements have led humor web sketches by Porta dos Fundos to become one of the most viewed contents among Brazilian channels on YouTube. In order to understand how the founders managed to reach this result among viewers, we are doing a survey on the channel founders’ origins and their professional influences, especially when it comes to television. The knowledge achieved on media was extremely important so that they could eventually construct an audiovisual product which is so familiar to the audience. The methodology of the study will be the analysis of some of the characteristics of web sketches, such as lighting, makeup, costumes, script, decoupage and duration of videos. This procedure seeks to map the format of the web sketches and to indicate how these elements are relevant in order to build an audiovisual product that can contribute to attract the attention of the viewer. Furthermore, we will compare the features of the web sketches from Porta dos Fundos with three audiovisual products, Zorra (RGTV), Tá no Ar: a TV na TV (RGTV) and Parafernalha (YouTube), to evaluate differences and similarities in the construction of sketches for television and the internet. We hope that, by comparing these products, we will be able to point out whether YouTube channels such as Porta dos Fundos may have influenced the construction of television programs and how the producers of both media have been adapting their techniques and skills in order to create audiovisual products that can attract the attention of the viewer. In order to help the understanding of the concepts, we will use as reference the following authors: Gazzaley and Rosen (2016) when it comes to the problem of attention in a world with infinite access to data, Tofler (1995) and Castells (1999; 2010) regarding the age of information, Butler (2010) on audiovisual language and Ramos (2004), regarding television.